PENGARUH INTERVENSI ULTRASOUND TERHADAP PERUBAHAN NYERI CARPAL TUNNEL SYNDROME DI KLINIK FISIOTERAPI SAYANG JATINANGOR TAHUN 2022 - Ratu Karel Lina; Abdurahman Berbudi B.L.; Sri Parwati (Jurnal Fisioterapi dan Kesehatan Indonesia, 2022)
Background: Carpal Tunnel Syndrome is a weakness in the hand accompanied by pain in the distribution area of the median nerve with the most frequent occurrence, chronic, and characterized by hand pain at night, paresthesias of the fingers that receive innervation from the median nerve, weakness and atrophy. thenar muscle. Methods: The research design used is a pre and post experimental design research method. With a total sample of 19 people taken from Carpal Tunnel Syndrome patients at the Sayang Jatinangor Physiotherapy Clinic. This research was conducted for 4 weeks with a total of 8 times. Analysis was used with the Wilcoxon test. Results: Research and statistical tests showed that the p value (0.000) < (0.05), there was sufficient evidence to state that the population median difference was different from 0, at the significance level = 0.05. Conclusion: There is a decrease in pain before and after the administration of ultrasound intervention in Carpal Tunnel Syndrome patients.